Strong Interlayer Coupling in Twisted Transition Metal Dichalcogenide Moiré Superlattices. Issue 16 (10th March 2023) - Zheng, Haihong; Guo, Hongli; Chen, Shula; Wu, Biao; Li, Shaofei; He, Jun; Liu, Zongwen; Lu, Gang; Duan, Xidong; Pan, Anlian; Liu, Yanping
Abstract: Moiré superlattices in twisted van der Waals materials offer a powerful platform for exploring light–matter interactions. The periodic moiré potentials in moiré superlattices can induce strongly correlated quantum phenomena that depend on the moiré potential associated with interlayer coupling at the interface. However, moiré superlattices are primarily prepared by mechanical exfoliation and manual stacking, where the transfer methods easily cause interfacial contamination, and the preparation of high‐quality bilayer 2D materials with small twist angles by growth methods remains a significant challenge. In this work, WSe2 /WSe2 homobilayers with different twist angles by chemical vapor deposition (CVD), using a heteroatom‐assisted growth technique, are synthesized. Using low‐frequency Raman scattering, the uniformity of the moiré superlattices is mapped to demonstrate the strong interfacial coupling of the CVD‐fabricated twist‐angle homobilayers. The moiré potential depths of the CVD‐grown and artificially stacked homostructures with twist angles of 1.5° are 115 and 45 meV (an increase of 155%), indicating that the depth of moiré potential can be modulated by the interfacial coupling. These results open a new avenue to study the modulation of moiré potential by strong interlayer coupling and provide a foundation for the development of twistronics. Abstract : A strong interlayer‐coupled WSe2 /WSe2 homostructure is grown by chemical vapor deposition using a heteroatom‐assisted approach to overcome the stacking‐free energy, showing a uniform moiré superlattice and strong interfacial coupling. The interlayer coupling can be adjusted by altering the twist angle, enabling the investigation of a variety of novel physical phenomena, which is expected to realize single‐photon emission and promote the development of coherent quantum light emitters.